Public awareness toward promotional activities on SOCSO’s benefits and services / Siti Nazariah Wahab - Wahab, Siti Nazariah (2010)
This research conducted focusing on the “Public awareness toward promotional activities on SOCSO’s benefits and services”. As a social security in Malaysia, SOCSO realize that public awareness is very important to ensure that all working Malaysian citizens have knowledge about SOCSO’s benefits and services. Malaysian should know about schemes that provide by SOCSO. There are still grouses that publics still not aware towards SOCSO and the benefits and services provide by SOCSO. In support of the government’s endeavour, SOCSO is committed to create a caring society. The main objectives of this study are (1) to determine the level of awareness among publics toward benefits and services provide by SOCSO, (2) to rank the element of promotional activities toward publics’ awareness and (3) to find the strategies that SOCSO can implement in order to create awareness among publics towards benefits and services provide by SOCSO. The respondents of this study were public people including teenagers and adults in Rawang area. 30 questionnaires had been distributed among them. The researcher had used convenience sampling as a sampling technique. The process of analyzing and interpreting data has been presented with tables using method as reliability test, frequency and descriptive analysis. The researcher also had come out with few recommendations. The recommendation can be taken into consideration. By implementing these recommendations, the researcher optimism that it will help the SOCSO to better upgrade its performance and their management for future use that can increase public’s awareness towards their benefits and services.